Biosorption of Ni (II) by Schizosaccharomyces pombe: kinetic and thermodynamic studies - SAYAR, AHMET ALP; SAYAR, NİHAT ALPAGU; DURMAZ ŞAM, SELÇEN (SPRINGER, 2011)
The potential of the dried yeast, wild-type Schizosaccharomyces pombe, to remove Ni(II) ion was investigated in batch mode under varying experimental conditions including pH, temperature, initial metal ion concentration and biosorbent dose. Optimum pH for biosorption was determined as 5.0. The highest equilibrium uptake of Ni(II) on S. pombe, q(e), was obtained at 25 degrees C as 33.8 mg g(-1). It decreased with increasing temperature within a range of 25-50 degrees C denoting an exothermic behaviour. Increasing initial Ni(II) concentration up to 400 mg L-1 also elevated equilibrium uptake. No more adsorption took place beyond 400 mg L-1. Equilibrium data fitted better to Langmuir model rather than Freundlich model. Sips, Redlich-Peterson, and Kahn isotherm equations modelled the investigated system with a performance not better than Langmuir. Kinetic model evaluations showed that Ni(II) biosorption process followed the pseudo-second order rate model while rate constants decreased with increasing temperature. Gibbs free energy changes (Delta G degrees) of the system at 25, 30, 35 and 50 degrees C were found as -1.47E + 4, -1.49E + 4, -1.51E + 4, and -1.58E + 4 J mol(-1), respectively. Enthalpy change (Delta H degrees) was determined as -2.57E + 3 J mol(-1) which also supports the observed exothermic behaviour of the biosorption process. Entropy change (Delta S degrees) had a positive value (40.75 J mol(-1) K-1) indicating an increase in randomness during biosorption process. Consequently, S. pombe was found to be a potential low-cost agent for Ni(II) in slightly acidic aqueous medium. In parallel, it has been assumed to act as a separating agent for Ni(II) recovery from its aqueous solution.
Keywords: Biosorption; Schizosaccharomyces pombe; Adsorption isotherms; Process kinetics and thermodynamics; HEAVY-METALS; ASPERGILLUS-NIGER; SACCHAROMYCES-CEREVISIAE; RHIZOPUS-ARRHIZUS; NICKEL(II) IONS; ADSORPTION; REMOVAL; EQUILIBRIUM; SORPTION; COPPER